HAMBATAN SISWA DALAM MENYELESAIKAN SOAL MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) BERDASARKAN KEMAMPUAN PEMECAHAN MASALAH PADA SISWA KELAS VIII SMP NEGERI 1 SUNGAI KAKAP - Winda Winarti; Muhamad Firdaus; Hartono Hartono (Student Scientific Creativity Journal, 2023)
This study aims to describe students' learning barriers in solving SPLDV questions based on problem solving abilities. This research uses descriptive qualitative research, and the sampling technique uses purposive sampling technique. This research was conducted at Sungai Kakap 1 Public Middle School, the data used were the results of researchers to clarify students' obstacles in answering questions based on problem-solving abilities with data sources, namely class VIII students of SMP 1 Sungai Kakap. Data collection techniques used measurement techniques, direct communication techniques and indirect communication techniques with data collection tools in the form of test questions, interview guides and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. In this study it was concluded that the students' barriers in the high group were wrong in determining the formula and wrong in the concept of completion, the students' barriers in the medium group were wrong in determining the formula, discrepancies in using the formula to answer a problem and did not re-examine the answers, and student barriers in the low group were unable to determine the formula and solve the problem on the question then also did not re-check the answer after completing the given question.